Price variation and transmission in beans consuming market of Southwest, Nigeria - Olanrewaju Omosehin; Babatunde Ekundayo; Oluyede Aturamu; Adewale Olutumise (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2021)
Nigeria's bean market is still characterized by inefficient and weak integration due to inadequate price information and market infrastructure. Therefore, the study investigates the price variation and transmission of beans markets in Nigeria's Southwest region. The study employed an average monthly price of white and brown beans in rural and urban markets spanning March 2014 to July 2019. Coefficient of variation (CV), Augmented Dickey-Fuller (ADF), Johansen co-integration test and Granger-Causality tests were the analytical tools used for the analysis. The results of CV indicated a spike variation of beans prices over the periods. Urban brown beans experienced the lowest variability of 1.56% in 2015, while rural brown beans experienced the highest variability of 30.03% in 2014. The co-integration test established a long-run dynamic between bean products of different varieties in the same market. However, it failed in the same products in different markets using a bivariate co-integration test. The multivariate co-integration test’s results affirmed that bean markets are strongly linked together in the long-run. The results of Granger-causality showed uni-directional and bi-directional causalities in the beans markets. Rural white beans assumed the lead position and formed the major price transmission in the beans’ markets in the area. Therefore, for more efficiency in the beans’ rural and urban markets, the government should design appropriate market strategies such as accessible market information and infrastructures.